Personality, Coping, and Well-Being for People Living with Chronic Hepatitis C. Issue 2 (April 2016) - Cellar, Douglas F.; Voster, Devon; Fetters, Rachel; Twitchell, Emily; Harper, Gary W.; Scott, Cotler
The present study examined the relationships between personality, coping strategies, and health ratings to extend past research to people living with chronic hepatitis C (HCV). Participants were 35 people (11 men, 24 women; M age = 49.6 yr., SD = 10.6) living with chronic hepatitis C for an average of 9.0 yr. ( SD = 6.0) since diagnosis. Participants provided descriptions of stressful situations and responded to a personality inventory, Ways of Coping Questionnaire scales (planful problem solving and escape-avoidance) and SF36 Health Survey scales measuring physical functioning and mental health. The stressful situations were judgmentally clustered into seven dimensions (diagnosis/mortality, disclosure, stigma, social and work role functioning, compounding problems, and no stress). Correlational analyses indicated strong negative relationships between escape–avoidance coping and health measures. Emotional Stability and Extraversion were positively related to both health variables, and Extraversion was negatively related to escape–avoidance coping. The results suggest that research from other contexts that has examined these relationships tended to generalize to people living with HCV.